Uncaria rhynchophylla ameliorates amyloid beta deposition and amyloid beta-mediated pathology in 5XFAD mice. (December 2018) - Shin, Soo Jung; Jeong, Yuon; Jeon, Seong Gak; Kim, Sujin; Lee, Seong-kyung; Choi, Hong Seok; Im, Cheong Su; Kim, Seong Hee; Kim, Soo Hwan; Park, Jae Ho; Kim, Jin-il; Kim, Jwa-Jin; et al.
Abstract: One of the pathological hallmarks of Alzheimer's disease (AD) is the abnormal aggregation of amyloid beta (Aβ) peptides. Uncaria rhynchophylla (UR), one of the Uncaria species, has long been used to treat neurodegenerative disease. In particular, it has been reported that UR inhibits aggregation of Aβ in vitro. However, little is known about the histological effects of UR treatment on Aβ pathology in AD animal models. In the present study, we investigated the effect of UR on Aβ aggregation, Aβ-mediated pathologies and adult hippocampal neurogenesis in the brain of 5XFAD mice. First, using the thioflavin T assay and amyloid staining, we demonstrated that UR treatment effectively inhibited Aβ aggregation and accumulation in the cortex and subiculum. Second, immunofluorescence staining showed that administration of UR attenuated gliosis and neurodegeneration in the subiculum and cortex. Third, UR treatment ameliorated impaired adult hippocampal neurogenesis. The present results indicate that UR significantly alleviates Aβ deposition and Aβ-mediated neuropathology in the brain in 5XFAD mice, suggesting the potency of UR as a preventive and therapeutic agent for AD. Highlights: Uncaria rhynchophylla (UR) inhibited Aβ aggregation and accumulation. UR alleviated neuroinflammation induced by Aβ. Treatment of UR relieved synaptic and neuronal loss in AD mice. UR attenuated impaired hippocampal neurogenesis induced by Aβ.